Animation and America - Wells, Paul, 1961- (BAAS paperbacks., 2002)
"In Animation and America, Professor Paul Wells looks at animation in the United States afresh. He discusses the distinctiveness of the cartoon form and the myriad other types of animation production, insisting upon the 'modernity' of the form and its crucial importance as a barometer of the social conditions in which it was made, and which it reflects." "The book does not work as an orthodox history of animation in America, but rather uses animation as a way of discussing personal, social and political change, concentrating on the ways in which the form continues to grow, experiment and remain subversive while gaining increasing popular acclaim and recognition. Animation is now in the vanguard of visual culture per se: it occupies an important position in representing both the outcomes and impacts of new technologies - as it has always done - but it has also laid the foundations for a new understanding of social and artistic practice."--Jacket